Transforming the transformation? the East European radical right in the political process - Minkenberg, Michael (Routledge studies in extremism and democracy, 2015)
The book aims to take a closer look at the significance of radical right parties, along with other organizations, in terms of their involvement in the political process of the new democracies. In particular, the book attempts to highlight (a) the radical right's interaction with other political actors (parties, governments, interest groups) in the respective country and (b) the effects of such interaction with regard to agenda setting and/or policies in "loaded" policy fields (minorities and immigration, law & order, religion, territorial issues, democratization). The main theme of the book is the role of radical right parties and other actors in political processes, in interaction with other actors (parties) and with a measurable outcome (policies, election results, regime changes) which indicate shifts away from the liberal-democratic order institutionalized in the course of the post-Communist transformation. This is done by looking cross-nationally at particular facets and themes (for example coalition formation or policy outputs in countries where the radical right has been in governmental office) and by in-depth analysis of country cases. This book will be of interest to undergraduate and postgraduate students, as well as scholars, of politics and far right studies"-- Provided by The Publisher